1998
DOI: 10.1159/000009985
|View full text |Cite
|
Sign up to set email alerts
|

Dysuria due to Bladder Distortion after Repeat Cesarean Section

Abstract: Abnormalities of the lower urinary tract resulting from cesarean section are rare. We present a patient who developed urinary frequency, nocturia and acute pains in the late phase of micturition which we think was due to bladder distortion after repeat cesarean section. She was diagnosed cystographically and treated successfully by bladder flap release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
(4 reference statements)
1
2
0
Order By: Relevance
“…On average, 1 patient received 5.75 U of Red Blood Cell Concentrate (RBCC), and 2.67 U of fresh frozen plasma. Other authors reported similar values of RBCC (96.0% and 84% cases required transfusions during obstetric hysterectomy) [21,23].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…On average, 1 patient received 5.75 U of Red Blood Cell Concentrate (RBCC), and 2.67 U of fresh frozen plasma. Other authors reported similar values of RBCC (96.0% and 84% cases required transfusions during obstetric hysterectomy) [21,23].…”
Section: Discussionsupporting
confidence: 56%
“…It is recommended to check the ureters patency at the close of each operation during which there was a risk of injury [2,15]. Among complications after hysterectomy at caesarean section or after delivery, ureteral injury was reported in 3% of women [23]. In the present analysis, 1 case of ureteral injury occurred during hysterectomy performed at caesarean section; among hysterectomies performed during caesarean section and in the puerperium it accounted for 2.6% cases.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation